Environmental and Socio-Economic Impacts of Coal-Fired Payra Thermal Power Plant (Bangladesh Journal of Physics, 2025)
Coal-based thermal power plants are essential for meeting the growing energy demands of developing countries like Bangladesh. However, their environmental impact, particularly on agriculture and ecosystems, raises serious concerns. This study assesses the environmental consequences of the Payra Thermal Power Plant in the Kalapara region, focusing on air, water, and soil quality, as well as agricultural productivity and biodiversity. This study analyzed key pollutants (SO₂, NOx, PM, and heavy metals from fly ash) and their impact on soil fertility, crop yield, and aquatic biodiversity. Additionally, greenhouse gas emissions such as carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O) contribute to climate change and local air pollution. Field data were collected through air and water quality monitoring, soil analysis, and structured farmer surveys within a 9 km radius of the plant. The findings indicate a decline in agricultural output, contamination of water bodies, and disruptions in fish populations, particularly the economically significant Ilish fish. The study highlights the urgent need for mitigation strategies, including advanced emission control technologies, sustainable waste management, and stricter environmental regulations, to minimize ecological degradation while maintaining energy production.Bangladesh Journal of Physics, Vol. 32, Issue 1, pp. 1 – 12, June 2025